Whole Transcriptome Analysis Reveals Heterogeneity in B Cell Memory Populations in Patients With Juvenile Idiopathic Arthritis-Associated Uveitis - Roos A. W. Wennink; Roos A. W. Wennink; Aridaman Pandit; Anne-Mieke J. W. Haasnoot; Anne-Mieke J. W. Haasnoot; Sanne Hiddingh; Viera Kalinina Ayuso; Nico M. Wulffraat; Bas J. Vastert; Timothy R. D. J. Radstake; Timothy R. D. J. Radstake; Joke H. de Boer; et al. (Frontiers in Immunology, 2020)
PurposePatients with juvenile idiopathic arthritis (JIA) are prone to developing chronic anterior uveitis (JIA-U+). Although several risk factors for JIA-U+ have been identified, the underlying etiology is poorly understood. Histopathological studies demonstrate B cell infiltrates in eye tissues of patients with JIA-U+.MethodsWe performed transcriptome profiling of peripheral blood CD19-positive B cells taken from 14 cases with JIA-U+, 13 JIA cases without uveitis (JIA-U−), and five healthy controls. Deconvolution-based estimation was used to determine the immune cell fractions for each sample.ResultsDeconvolution results revealed that naive B cells made up on average 71% of the CD19-positive cell fractions analyzed. Differential expression analysis identified 614 differentially expressed genes (DEGs) between the groups at nominal significance and six genes at a false discovery rate of 5% (FDR < 0.05). Head-to-head comparison of all JIA-U− versus JIA-U+ revealed no DEGs in the CD19+ B cell pool (FDR < 0.05). However, principal component analysis based on a panel of key genes for B cell subsets revealed that JIA-U+ cases bifurcate into distinct clusters, characterized by markedly disparate expression for genes associated with specific memory B cell populations. CIBERSORT analysis of the overall transcriptome of the new uveitis cluster identified an increased proportion of memory B cells.ConclusionThese data show that JIA-U− and JIA-U+ have a globally similar transcriptome considering the global peripheral CD19-positive B cell pool. However, heterogeneity in B cell memory genes among cases with uveitis suggests a role for specific memory B cell subsets in the etiology of JIA-U+.